On the genus Scalopidia Stimpson, 1858 (Crustacea: Brachyura: Goneplacoidea: Scalopidiidae), with the description of one new genus and three new species - Ng, Peter K.l.; Castro, Peter (Zootaxa, 2013)
A revision of Scalopidia Stimpson, 1858 (Brachyura: Goneplacoidea: Scalopidiidae) has resulted in the description of two new species of Scalopidia from the Indian Ocean and Papua New Guinea, as well as a new genus and new species from Madagascar. The type species of Scalopidia, S. spinosipes Stimpson, 1858, is redescribed and Hypophthalmus leuchochirus Richters, in Lenz & Richters, 1881, is synonymised with S. spinosipes.